Perancangan User Interface dan User Experience Website Bengkel 21Motoshop Menggunakan Metode User Centered Design - Adi Israel Wilhelm Coendrad Rontgen Peday; Ajenkris Yanto Kungkun (CV Edujavare Publishing, 2025)
The development of information technology encourages workshop businesses to adopt digital solutions to improve customer service. However, many workshop websites are built without comprehensively considering User Experience (UX) and User Interface (UI) aspects, causing navigation difficulties and decreased customer satisfaction. This research aims to design the UI/UX of the 21 Motoshop Workshop website using the User-Centered Design (UCD) method to create an effective and user-friendly digital platform. The UCD method was applied through four stages: understanding the context of use through observation and surveys of 35 respondents, determining user needs both functional and non-functional, designing solutions using UML and system implementation based on CodeIgniter 4 with MySQL, and usability evaluation using the System Usability Scale (SUS). The research results show that the system functions well functionally with main features such as mechanic data management, products, transactions, and online booking. SUS testing resulted in an average score of 84.25 which falls into the